DEVELOPMENT OF PHYSICS MODULE BASED ON AL-QUR’AN VALUES TO IMPROVE SPIRITUAL ATTITUDE - Nur Igawati; Khaeruddin Khaeruddin; Jasruddin Jasruddin (Jurnal Pendidikan Fisika, 2023)
This research is development research where the background of this research is the aim of national education, namely creating students who are intelligent, have faith and are devoted to God Almighty and have noble morals. Developing a spiritual attitude is one way to realize the goal of national education, namely to form pious people. The aim of the research is to describe the validity of the physics module based on Al-Qur'an values, the practicality of the physics module based on Al-Qur'an values and the effectiveness of the physics module based on Al-Qur'an values. The subjects of this research were 24 students. This research uses the development of the ADDIE model (Analysis, Design, Development or Production, Implementation, and Evaluation). The instruments used in this research were module validation sheets, practitioner response questionnaires (educators/teachers and students), as well as student spiritual attitude questionnaires. Module eligibility criteria are seen from the aspect of validity. The practicality criteria are seen from the teacher's assessment and students' responses to the module, and the effectiveness criteria are seen from the increase in students' spiritual attitude test results. Based on the results of the analysis, a conclusion was obtained: the physics module based on Al-Qur'an values which was developed based on expert assessment was declared valid and suitable for use with minor revisions, the physics module based on Al-Qur'an values was reviewed from the responses of physics teacher practitioners and participants students are in the very good category, the effectiveness of the physics module based on Al-Qur'an values is seen from the spiritual attitudes of students which are analyzed using N-gain. The average score is 0.43, which is in the medium category, which means that there is an improvement in attitude. students' spirituality so it can be said that the physics module based on Al-Qur'an values developed is effective in improving students' spiritual attitudes.